Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-5 Division Properties of Exponents - Practice and Problem-Solving Exercises - Page 443: 20



Work Step by Step

RECALL: (i) $a^m \cdot a^n = a^{m+n}$ (ii) $a^{-m} = \dfrac{1}{a^m}, a\ne0$ (iii) $a^0=1, a\ne0$ Use the rules above to have: $=m^{3-(-1)}n^{2-3} \\=m^{3+1}n^{-1} \\=m^4 \cdot \dfrac{1}{n} \\=\dfrac{m^4}{n}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.